EVALUATION OF ESSENTIAL ATTRIBUTES IN THE FAMILY HEALTH STRATEGY: USERS' PERSPECTIVE - Borin, Emanoeli Rostirola; Silva, Clarissa Bohrer da; Trindade, Letícia de Lima; Reinehr, Karine Regina; Ascari, Rosana Amora; Barimacker, Saionara Vitória (Cogitare Enfermagem, 2024)
Objective: to evaluate the presence and extent of the essential attributes of Primary Health Care from the perspective of users of the Family Health Strategy. Method: this was a cross-sectional, quantitative study of 256 users of 26 family health units in Santa Catarina, Brazil, carried out between June and December 2021. A characterization questionnaire and the Primary Care Assessment Instrument were used. Descriptive and inferential statistics analysis was carried out. Results: users evaluated the units as having a sub-optimal score for the presence and extent of the essential attributes. However, users with health problems rated the essential score (p=0.001), the longitudinality attribute (p=0.024), and the comprehensiveness attribute (p=0.001) positively.). Conclusion: periodically evaluating the presence and extent of the attributes makes it possible to guide strengthening strategies and contributes to the continuous improvement of Primary Care, based on indicators for qualified health management, with the difference of considering the views of users.